Childhood and conceptions of childhood in Russian literature in the 21st century - Kuzminykh, Ksenia (Glottodidactica, 2021)
The article begins with an overview of the childhood conceptions found in literature for children’s and young people. The conception of childhood in the Enlightenment is directed towards the future. The characters are serious and strive to become better people. They are an example for the recipients. Romanticism, on the other hand, tries to undermine this idea, and evokes a golden age of childhood. The first type dominated Soviet literature for children and young people. This changed in the 21st century. The analysis of Sabitova’s, Emec’s, Wostokows’s, Krjukova’s, Murašova’s and Verkin’s novels shows how these childhood myths are successfully combined in modern books for children and young adults.